Practical Recommendations on the Improvement of the Effectiveness of Anti-Corruption Policy in Universities - Zamaletdinov, Radif R.; Yudina, Nadezhda P.; Lavrentyeva, Elvira I.; Savva, Lubov I.; Pugacheva, Natalya B. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the expansion of the scale of corruption in higher education. The purpose of the article is to develop practical recommendations for improving of anti-corruption policy's effectiveness at universities. The study involved 450 teachers, 1200 students from 140 Russian universities. The main results of the study are to identify the causes of bribery and popular tools of counteraction of corruption in universities, organizational and practical measures for improving of the anti-corruption policy's effectiveness (the creation of the university's anti-corruption environment, the formation of the stable orientation of students, faculty, staff of the university on anti-corruption activities, including in the content of higher education of teaching material about the anti-corruption policy). This study provides important findings. Firstly, the effectiveness of anti-corruption policy in universities is increased while forming of anticorruption outlook and anti-corruption attitudes among the entities of the educational process determining the intellectual and valuable-emotional attitude to corruption and influencing the readiness for anti-corruption activities. Secondly, the effectiveness of anti-corruption policy in universities is increased with the application of cognitive, activities-related, interactive and integrative methods' complex. Keywords: corruption in education, anti-corruption policy, anti-corruption environment. JEL Classifications: A12, A20, H52, I23